Research on Community Linkage Promotion Model of Children’s Physical Health Management - Zhou, Wenlong; xu, Jinsong; ma, Xiao (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
Due to the imperfection of community facilities, the linkage effect of the traditional community promotion model decreases. Therefore, a community linkage promotion model of children's physical health management is designed. Extracting the influencing factors of community linkage of children's physical health management, analyzing the feasibility of community linkage. Then realizing the community linkage promotion model. Comparative experiment is adopted to verify that the community linkage effect of the new model is better, and it has great promotion value.